(untitled) - Šamajová, Veronika; Dávid, Andrej; Žarnay, Pavel (Doprava a spoje, 2008)
The company Česko-saské přístavy (ČSP) was established on 1st October 2002 by Sächsische Binnenhäfen Oberelbe (SBO). After the shipping company Československá plavba labská had bankrupted in 2002 SBO took over its two inland ports in the Czech Republic (the port of Dečín and Lovosice). ČSP owns and operates these ports, cooperates on logistics chains with SBO